Linear Active Disturbance Rejection Control of Waste Heat Recovery Systems with Organic Rankine Cycles - Fang Fang; Hong Yue; Yeli Zhou; Jiancun Feng; Jianhua Zhang (Energies, 2012)
In this paper, a linear active disturbance rejection controller is proposed for a waste heat recovery system using an organic Rankine cycle process, whose model is obtained by applying the system identification technique. The disturbances imposed on the waste heat recovery system are estimated through an extended linear state observer and then compensated by a linear feedback control strategy. The proposed control strategy is applied to a 100 kW waste heat recovery system to handle the power demand variations of grid and process disturbances. The effectiveness of this controller is verified via a simulation study, and the results demonstrate that the proposed strategy can provide satisfactory tracking performance and disturbance rejection.